2017
DOI: 10.1111/rda.13111
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of ovarian transcriptomes between prolific and non‐prolific goat breeds via high‐throughput sequencing

Abstract: To increase the current understanding of the gene expression in the pre-ovulatory ovary and identify the key genes involved in the regulation of ovulation rate, we compared the transcriptomes of ovaries from the prolific Jintang black goat (JTG) and the non-prolific Tibetan goat (TBG) during the follicular phase using the Illumina RNA-Seq method. Three ovarian libraries were constructed for each breed. On average, we obtained approximately 49.2 and 45.9 million reads for each individual ovary of TBGs and JTGs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e, f). Approximately 37% of the DEgenes in the Uni-S vs Mul-S group and 41% in the Uni-L vs Mul-L group were reported to be associated with mammalian reproduction, such as TNFAIP6, MMP9, INSL3, LEPR, 3BHSD, LHCGR, ARL4C, CD36, CYP11A1, AMDHD1, SPOCK2, AMDHD1, MFAP5, CCL21, PTGFR, and SERPINA5 [23,[47][48][49][50][51][52][53][54][55][56][57][58][59][60]. Of these genes, TNFAIP6, CYP11A1, CD36, PTGFR, and SER-PINA5 were found to be associated with the ovulation rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about goat follicles. In goat, previous studies have identified the key genes involved in the regulation of ovulation rate and kidding rate by transcriptome analysis of goat ovaries, as well as the signaling pathways that affect ovulation and fertility [1,4,[23][24][25][26][27][28][29]. Studies on litter size of goats have shown that PDGFRB, MARCH1, KDM6A, CSN1S1, SIRT3, KITLG, GHR, ATBF1, INHA, GNRH1, and GDF9 might be candidate genes for goat reproductive traits [26,[30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq methods have been broadly utilized to determine DEGs or gene expression patterns, new transcripts, AS events and SNPS, and have empowered studies examining porcine [24,25], cattle [26,27] and mouse [28,29] testicular development. In goats, the profiles of ovarian [30,31], uterine [32,33] and testicular [34,35] tissues under different conditions were recently compared by RNA-Seq. However, limited data on testicular development in goats were available.…”
Section: Discussionmentioning
confidence: 99%
“…The high throughput sequencing approach is the most effective method for exploring of genetic resources. For goats, Zi et al identified 407 DEGs between prolific and non-prolific goat breeds and 171,829 versus 140,529 putative SNPs in Tibetan goats and Jintang black goats, respectively [ 31 ]. Yang et al explored hair follicle development-related microRNAs in cashmere goats at various fetal periods and found oar-let-7 and oar-miR-200 families in 55 days and 66 days of pregnancy samples had been notably up-regulated relative to those in 45 days of pregnancy samples [ 32 ].…”
Section: Discussionmentioning
confidence: 99%